Calculation Method for Critical Conditions of Distribution Network Considering Distributed Generation “Plug and Play” - Zhen JIANG; Li YU; Yanlu HUANG; Linhao YE; Shuang ZHENG; Guangfei GENG; Wei TANG (Zhongguo dianli)
In order to provide a theoretical basis for the realization of “plug and play” for distributed generation (DG) and other elements in the distribution network, from the macroscopic point of view, the first and second synergy systems of smart distribution networks that consider “plug and play” elements are established. Take distributed generation as an example, considering the constraints of load and DG power changes, voltage, line capacity, power flow reversal and DG power factor, a mathematical model for calculating the “plug and play” critical condition of distributed generation is proposed. And based on the consideration of load and DG power fluctuation, a critical condition execution strategy is proposed. Furthermore, through theoretical analysis, the constraint conditions in the critical condition model are equivalently simplified, and a fast estimation method for solving the “plug and play” critical conditions of DG is obtained. Taking the IEEE 33 nodes as an example, the proposed calculation method and simplified algorithm are compared and analyzed. The results show that the proposed simplified algorithm is feasible and can quickly estimate the DG “plug and play” critical conditions.